Commentary and critical discussion on ‘Decarbonizing the Chilean Electric Power System: A Prospective Analysis of Alternative Carbon Emissions Policies’ - Juan Carlos Osorio-Aravena; Jannik Haas; Arman Aghahosseini; Christian Breyer (International Journal of Sustainable Energy Planning and Management, 2022)
This paper is a commentary on ‘Decarbonizing the Chilean Electric Power System: A Prospective Analysis of Alternative Carbon Emissions Policies’ –an article published by Babonneau et al. in the Energies Journal. On the one hand, our aim is to point out and discuss some issues detected in the article regarding the literature review, modelling methods and cost assumptions, and, on the other hand, to provide suggestions about the use of state-of-the-art methods in the field, transparent and updated cost assumptions, key technologies to consider, and the importance of designing 100% renewable multi-energy systems. Furthermore, we end by highlighting suggestions that are key to modelling 100% renewable energy systems in the scientific context to contribute to expanding the knowledge in the field.